(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Cerebro vascular accident causes many health problems. Stroke causes death in the world as a third cause as well as a cause of dementia (Vascular dementia). It is also a cause of disability. Many revascularization techniques have been used in stroke units. New techniques in the management of stroke are intravenous thrombolysis, intraarterial treatment, bridging therapies and mechanical thrombectomy procedures. Seven randomized controlled trials will be reviewed in the article. We summarized that Intraarterial mechanical thrombectomy or Intraarterial thrombolytic therapy give good results. This conclusion is because of wider window period and high recanalization rates.